Alleviating Poverty Through One House One Farm Project in Bangladesh - Rahman, Muhammad Sayadur; Islam, Md. Monirul; Ullah, Mohammad Nur (Universitas Djuanda, 2024)
Poverty is a bad inhalation process in the economic breath system, especially at the rural level in Bangladesh. The one house one farm project was initiated to alleviate poverty in Bangladesh as an initiative of Prime Minister Sheikh Hasina. The project focuses on rural households generating income through family farming with e-financial inclusion or online banking opportunities. The study focuses on the fundamental understanding and reasons for the One House One Farm project. The study follows a generic qualitative method with secondary data sources, including the website of The Project, newspaper articles, and journal articles, to indicate what, how, and why questions. With some beneficiaries' statements, an ethnographic study is conducted as another data collection source. The study introduces a thematic mode of analysis that covers the explanation of the pattern of the One House One Farm project and gives a general idea about the background. The study finds that the One House One Farm project was a primary and better initiative for alleviating or eradicating poverty in Bangladesh, which helps to focus on achieving Sustainable Development Goal- 01. Besides the main target of alleviating or eradicating poverty in Bangladesh, this project helped rural households create a basement for generating income and being free from dependency.